Investigating Particle Acceleration in the Wolf–Rayet Bubble G2.4+1.4 - Prajapati, Prachi (2019)
The supersonic winds produced by massive stars carry a large amount of kinetic power. In numerous scenarios such winds have been proven to produce shocks in which relativistic particles are accelerated emitting nonthermal (NT) radiation. Here, we report the first detection of NT emission from a single stellar bubble, G2.4+1.4, associated with a WO star. We observed this source with the upgraded Giant Meterwave Radio Telescope in Band 4 (550-850 MHz) and Band 5 (1050-1450 MHz). We present intensity and spectral index maps for this source that are consistent with synchrotron emission (average spectral index, α = -0.83 ± 0.10). The fraction of the available kinetic wind power that is converted into cosmic-ray acceleration is estimated to be of the order of a few percent. This finding constitutes an observational breakthrough and gives new insight on the NT physical processes taking place in the environments of isolated massive stars. In particular, our results show that non-runaway isolated massive stars are capable of accelerating relativistic particles and are therefore confirmed as sources of Galactic cosmic rays.